Tomorrow never dies [videorecording (DVD)] - Spottiswoode, Roger; Pryce, Jonathan; Brosnan, Pierce; Yeoh, Michelle, 1963-; Dench, Judi, 1934- (Fox Home Entertainment, 2012)
Bond must prevent a tremendous global disaster when the superpowers are pitted against one another by a criminal mastermind who is manipulating world events through his media empire in order to corner the market on his next planned news story: global pandemonium!